Crescimento e desenvolvimento de mudas de cravina de jardim com diferentes substratos - Milani, Marília (2012)
The cravina is an excellent plant to build up gardens due to its early flowering, abundant flowering and great performance in spring and autumn, periods with fewer options of flowering plants with such end. The present work aimed to evaluate the growth and development of seedlings of cravina in gardens with different substrates. The study was carried out in greenhouse at the Federal University of Santa Maria, RS. The experimental design was entirely randomized, with seven substrates: 1 – 50% soil + 50% rice husk ash; 2 – 80% soil + 20% earthworm castings; 3 – 80% rice husk ash + 20% earthworm castings; 4 – 40% soil + 40% rice husk ash + 20% earthworm castings; 5 – 100% peat; 6 – 100% commercial substrate Mecplant®; 7 – 50% peat + 50% rice husk ash. Each, with 56 plants, totalizing 392 plants evaluated. 28-day-old seedlings of Dianthus chinensis L. ‘Dianthus F1 Diamond’, developed by Sakata® were used. The physical and chemical characteristics were evaluated and in the plants the number of leafs and of nodes, height, the cycle up to the differentiation were evaluated until first bud appear and the coverage of the substrate. The final assessment of the experiment was carried out when the bud of main stem was opened, and 20 variables of production, the optimum sample size and the concentration and content of nutrients of shoot were determined. Growth curves were adjusted by the logistic model for height of plant and number of leaves, in different substrates, in function of accumulated thermal time. The substrate 6 was superior to the others, in the following variables: coverage of the substrate, number of branches and buds, leaf area of branches and total of shoot, diameter of main stem of 5 and 10cm from the base of the substrate, fresh and dry phytomass of branches, fresh phytomass of main stem and fresh and dry phytomass total of shoot. The substrate 1 presented the longer production cycle up to the first bud to appear, 74 and 57 days, respectively and bigger plastochron, 94,09ºC day node-1. There was a variation in the sample size regarding the substrate and the observed variable. The sample size of the reproductive variable, number of buds, was bigger than the vegetative variables. For a minimum significant difference between two means (D%) of 20%, the substrate 1 was the one which presented the biggest sample size in 15 variables, once for the number of branches, fresh and dry phytomass of branches it presented the biggest sample size, 298 plants. In a general way, the growing curves showed good quality adjust to the logistic model. The substrate Mecplant® is indicated to produce seedling of cravina for gardens, because it offerd quality in the produced seedlings.